Determination of Destination Competitiveness: A Qualitative Analysis on Malaysiain Convention Torist - Hamrila, Abdul Latip; Lim, Suzie S.Y.; Ahmad Hajazi, Mohd Uzairi (ATRA, 2017)
Despite extensive empirical research linking organizational capability and competitiveness in the context of manufacturing companies, little attention has focused on the service sector, particularly the convention tourism sector. Convention tourism represents a growing and most desirable segment in Asia’s tourism industry. Many host destinations recognize this high-yield market, thus making the competition in the segment greater. Foresee new opportunities for Malaysia to tap into the convention tourism sector, the identification of the industry’s competitive advantages becomes an important step towards successful development in Malaysia. Based on Porter’s Diamond model, this paper makes an assessment on the competitive advantages that affect the convention tourism sector. Using qualitative approach, the components are analyzed carefully, comparing the competition among the four key markets in Malaysia namely Kuala Lumpur, Penang, Sarawak, and Sabah. Through in-depth interviews with focal industry participants, the responses then have been analyzed using cross-case analysis and develop causal network modeling to visualize the linkages between the elements of convention tourism competitiveness. The results indicate that firm strategy, structure and rivalry; demand conditions; and related and supporting industries contribute to the competitiveness of convention tourism industry. The results also highlighted that factors related to qualified, well-trained human resources and locality access should be considered critically in order to boost the performance of the sector